1.   Given f(x) = 3x + 2x - 2 and g(x) = 4x + 1, find
    A. B. 3x2 + 6x - 1
    C. D. 3x2 - 2x - 3
    Hint

  2.   Find (x) if f(x) = 3x2 + 1 and g(x) = 2x + 3.
    A. 12x2 - 36x + 28 B. 6x2 - 5
    C. 6x2 + 5 D. 12x2 + 36x + 28
    Hint

  3.   Find the first three iterates, x1, x2, and x3, of the function
f(x) = 3x - 1 for an initial value x0=1.
    A. 2, 5, 14 B. 5, 14, 41
    C. -4, -13, -40 D. 8, 23, 88
    Hint

  4.   Given f(x) = x-5 and g(x) = x2+ 3,find (f · g)(x).
    A. x3 5x2 +3x -15 B. 4x3 2x
    C. x3 +5x2 +3x-15 D. x2 2x-15
    Hint

  5.   Find the first three iterates of the function g(x) = x2 + x for an initial value of x0 = 1.
    A. = 2
= 6
= 42

B. = 2
= 6
= 12

    C. = 0
= 2
= 4

D. = 2
= 6
= 36

    Hint